ADSC-conditioned media elicit an ex vivo anti-inflammatory macrophage response. (November 2018) - Kruger, Maria Jacoba; Conradie, Maria Martha; Conradie, Magda; van de Vyver, Mari
Abstract : Obesity-associated inflammatory mechanisms play a key role in the pathogenesis of metabolic-related diseases. Failure of anti-inflammatory control mechanisms within adipose tissue and peripheral blood mononuclear cells (PBMCs) have been implicated in disease progression. This study investigated the efficacy of allogeneic adipose tissue-derived mesenchymal stem cells conditioned media (ADSC-CM) to counteract persistent inflammation by inducing an anti-inflammatory phenotype and cytokine response within PBMCs derived from patients with and without metabolic syndrome. Forty-six ( n  = 46) mixed ancestry females (18–45 years) were subdivided into (a) healthy lean (HL) ( n  = 10) (BMI <25 kg/m 2 ), (b) overweight/obese (OW/OB) (BMI ≥25 kg/m 2, <3 metabolic risk factors) ( n  = 22) and (c) metabolic syndrome (MetS) (visceral adiposity, ≥3 metabolic risk factors) ( n  = 14) groups. Body composition (DXA scan), metabolic (cholesterol, HDL, LDL, triglycerides, blood glucose) and inflammatory profiles (38-Plex cytokine panel) were determined. PBMCs were isolated from whole blood and treated ex vivo with either (i) autologous participant-derived serum, (ii) ADSCs-CM or (iii) a successive treatment regime. The activation status (CD11b+) and intracellular cytokine (IL6, IL10, TNFa) expression were determined in M1 (CD68+CD206−CD163−) and M2 (CD68+CD163+ CD206+) macrophage populations using flow cytometry. ADSC-CM treatment, promoted a M2 macrophage phenotype and induced IL10 expression, this was most pronounced in the OW/OB group. This response is likely mediated by multiple complementing factors within ADSC-CM, yet to be identified. This study is the first to demonstrate the therapeutic potential of ADSC-CM to restore the inflammatory balance in immune compromised obese individuals.